A deficiency screen of the major autosomes identifies a gene (matrimony) that is haplo-insufficient for achiasmate segregation in Drosophila oocytes. - Harris, D.; Orme, C.; Kramer, J.; Namba, L.; Champion, M.; Palladino, M.J.; Natzle, J.; Hawley, R.S. (Genetics, 2003)
In Drosophila oocytes, euchromatic homolog-homolog associations are released at the end of pachytene, while heterochromatic pairings persist until metaphase I. A screen of 123 autosomal deficiencies for dominant effects on achiasmate chromosome segregation has identified a single gene that is haplo-insufficient for homologous achiasmate segregation and whose product may be required for the maintenance of such heterochromatic pairings. Of the deficiencies tested, only one exhibited a strong dominant effect on achiasmate segregation, inducing both X and fourth chromosome nondisjunction in FM7/X females. Five overlapping deficiencies showed a similar dominant effect on achiasmate chromosome disjunction and mapped the haplo-insufficient meiotic gene to a small interval within 66C7-12. A P-element insertion mutation in this interval exhibits a similar dominant effect on achiasmate segregation, inducing both high levels of X and fourth chromosome nondisjunction in FM7/X females and high levels of fourth chromosome nondisjunction in X/X females. The insertion site for this P element lies immediately upstream of CG18543, and germline expression of a UAS-CG18543 cDNA construct driven by nanos-GAL4 fully rescues the dominant meiotic defect. We conclude that CG18543 is the haplo-insufficient gene and have renamed this gene matrimony (mtrm). Cytological studies of prometaphase and metaphase I in mtrm hemizygotes demonstrate that achiasmate chromosomes are not properly positioned with respect to their homolog on the meiotic spindle. One possible, albeit speculative, interpretation of these data is that the presence of only a single copy of mtrm disrupts the function of whatever "glue" holds heterochromatically paired homologs together from the end of pachytene until metaphase I.